2021
DOI: 10.1039/d1ra06260c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of medical hydrophilic and antibacterial silicone rubber via surface modification

Abstract: Surface modification of silicone rubber to enhance hydrophilicity and antibacterial effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…30 Furthermore, studies have also shown that a hydrophilic surface or coating shows better antibacterial activity. 31 This is because a hydrophilic surface increases the contact area of the antibacterial material with the pathogens. 30 Bacteria coming in contact with a hydrophilic surface get adsorbed on the surface very easily through rapid spreading, thereby exposing it to a larger surface area of the antibacterial material.…”
Section: Fabrication and Characterization Of Mcp Glycosheet-coated Ss...mentioning
confidence: 99%
“…30 Furthermore, studies have also shown that a hydrophilic surface or coating shows better antibacterial activity. 31 This is because a hydrophilic surface increases the contact area of the antibacterial material with the pathogens. 30 Bacteria coming in contact with a hydrophilic surface get adsorbed on the surface very easily through rapid spreading, thereby exposing it to a larger surface area of the antibacterial material.…”
Section: Fabrication and Characterization Of Mcp Glycosheet-coated Ss...mentioning
confidence: 99%
“…[80] It is described that the in-crease of surfaces hydrophobicity can reduce the interaction between the bacteria and the surface by the formation of a hydration layer due the higher tension between hydrophilic surfaces with water. [81,82] Indeed, Yuan et al [83] showed that surfaces with CA of about 90°presented lower ABA of E. coli, decreasing the adhesion with a lower or higher wettability. Consequently, it is expected that surfaces with higher CA present lower bioaffinity.…”
Section: Assessment Of Antibacterial Adhesionmentioning
confidence: 99%
“…Medical-grade silicone (MGS) is the primary material in endotracheal prostheses. MGS has attractive properties such as chemical inertness, water and temperature resistance, biocompatibility, and flexibility [ 11 ]. The constant contact between the inhaled air passing through the airway prosthesis and the tracheal underlying mucosa promotes the accumulation of biofilms composed of bacteria and fungi.…”
Section: Introductionmentioning
confidence: 99%